ANALISIS KONDISI SOSIAL EKONOMI PEREMPUAN MISKIN DI KECAMATAN BLANG BINTANG, ACEH BESAR - Yusniati Yusniati; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2021)
Abstract This study aims to analyze the socio-economic conditions of poor women in Blang Bintang sub-district, Aceh Besar district. This study uses primary data obtained by simple random sampling. The model used to analyze this goal is with Multiple Linear Regression. The results showed that the age result had a negative and significant effect. Employment coefficient was found to have a positive and significant effect. Meanwhile, the number of dependent children has a significant negative effect on the income of poor women. The recommendation of this research is that the government can provide skills training and also create jobs according to the training provided. The capital provided should really be used to build a business. Keywords: Poorness, Poor women, Earnings, Age, Education.